Impacto do atendimento integral às vitímas de violência sexual em Hospital Universitário - Baptista, Marcus Vinícius (2024)
Introduction: Sexual violence (SV) is a serious public health issue with immediate and long-term consequences such as unwanted pregnancy, abortion, gynecological complications, sexually transmitted infections, depression, and Post-Traumatic Stress Disorder, among others. Therefore, the need for a multi-professional approach in the care of women who experience SV is directly related to the complexity of the situation and the multitude of consequences imposed on the victims. To address SV victims, the Acolher project was created in 2001 at the Hospital de Base in São José do Rio Preto (HB), as there is still a limited number of specialized services for SV cases, and little is known about the implementation, quality, and effectiveness of established work processes. Objectives: To describe the care provided by the Acolher project; to characterize the epidemiological profile of the victims; to analyze the provided care, highlighting the acceptance of prophylaxis for sexually transmitted diseases (STDs) and pregnancy; and assess adherence to the follow-up offered by the multidisciplinary team. Casuistry and Methods: Descriptive, retrospective study, with documentary analysis of information on the care of SV victims from 2001 to 2021. Data from 680 victims were analyzed, obtaining percentages and prevalences among different variables. The Kolmogorov-Smirnov test was used for inferential statistical analysis of quantitative variables to check data normality. The Mann-Whitney test was then applied. Frequency comparisons were obtained with the Classic Chi-square test and the Kappa concordance test A P value 0.05 was considered statistically significant. Results: Most victims were female (87.79%), with 58.23% in the age group of 0 to 14 years. The incidence was higher in individuals with incomplete elementary education (50.44%). Alcohol/drug use was observed in 34.71%, and 56.91% sought care within 72 hours. Prophylaxis was performed in 36.32%. After the event, 47.50% discontinued follow-up. Statistical analyses revealed significant correlations, such as between nighttime and alcohol use (p< 0.01). The association between substance use and time of care emphasizes the need for prevention strategies and adequate support for victims, considering the intersection of these issues. These results highlight the challenges in providing care to SV victims, emphasizing the importance. Conclusion: The high dropout rate highlights the need for personalized support strategies. Interventions must create environments of trust, train professionals and strengthen specialized services. Educational programs and public awareness are crucial to promoting treatment adherence. A centralized service is proposed, including competent authorities, immediate assistance, emotional analysis, and follow-up through efficient channels to improve compliance and continuity of care for victims.